Pemanfaatan KUR, Pembentukan Koplay, Penggunaan saluran distribusi daring (online): Solusi Peningkatan Usaha Kampung KB Layang Layang Kota Palembang - Tien Yustini; Lasmiana Lasmiana (MBIA, 2019)
The business of the KB Village community has enormous potential to continue to grow. Support from the government, good family relations in the community, enthusiasm to learn and improve themselves, and the unique name of the village as a brand contribute to the advancement of SMEs in the KB Village community. This research is expected to be able to provide solutions on how to increase the business and income of Layang Layang KB Village UPPKS. This research method is a Census (survey), where all KB Village Cadres who have businesses both micro and small scale are used as research samples (saturated samples). and by using qualitative descriptive analysis, this research shows that: 1). Utilization of KUR bank products can be a solution to the problem of limited business capital faced by the Layang-Layang village community. Our visit also educated the public on how to manage good finances, from separating personal / household needs from business needs, to setting aside operating profits to be used as business capital. 2). The kite production process is divided up to sales that depend on collectors, making the formation of community associations as a solution to better manage the production process, more efficient sales process, to the flexibility of determining the final sale price of the kite product. Sales that do not depend on collectors will be able to maximize profit potential for the community, not shrinking by a long business process. 3). The introduction of online sales channels is the right solution so that people's products are more quickly recognized, expand target markets without having to incur expensive costs, and increase sales. Enthusiastic and understanding of the community from the training in the use of online shops: The Bukapalak that we held, convinced our group that the businesses of the KB village community have the potential to advance. 4). The problem of kite seasonal products faced by the community can be dealt with by developing products, creating differentiation of kite products from the KB village with other kite products, and starting to think creatively.